Towards a strategy for the recovering of the Mediterranean monk seal in the Adriatic-Ionian Basin - Panou, Aliki; Giannoulaki, Marianna; Varda, Dušan; Lazaj, Lorela; Pojana, Giulio; Bundone, Luigi (Frontiers in Marine Science, 2023)
Occasional but recurrent sightings indicate that the endangered Mediterranean monk seal is still present in most of its historical range within the Adriatic-Ionian region in the central Mediterranean Sea. However, in most of the adjacent countries, the species’ abundance and distribution are practically unknown. An actively reproducing sub-population with a minimum of 25 adult/sub-adult seals lives in the Greek central Ionian Sea. The latter can form a nucleus from which the entire Adriatic-Ionian Basin could be re-colonized if adequate conservation measures are implemented throughout the area and in a coordinated manner. We examine the historical presence in the region as a baseline for providing a benchmark for conservation. We further look into the species’ habitat availability, possibilities for a rapid population assessment and various parameters that are considered crucial for its conservation, such as the existence of Marine Protected Areas (MPAs), corridors for connectivity purposes as well as needs for raising public awareness. We recommend a series of interlinked actions within the framework of a conservation strategy the implementation of which will ensure the conditions for maintaining ecologically, demographically, and genetically viable sub-populations of this species emblematic for the entire Mediterranean Sea. To achieve this goal, a coalition of partners from this area is required in order to adopt the strategy and jointly implement the measures required.